STUDI OF LOCAL CAPACITY IN DISASTER MANAGEMENT IN TOLIKARA REGENCY - Sitorus, Yannice Luma Marnala; Nurmaningtyas, Anggia Riani; Usman, Syamsuddin; Yanthy, Normalia Ode (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Disaster events that have often occurred recently in Indonesia reminded us of the importance of disaster mitigation that must be carried out by all stakeholders to avoid greater casualties. Local governments are representatives of the state who must be present when their citizens need assistance when a disaster occurs and must play a more dominant role in disaster mitigation, especially in relatively isolated areas with limited stakeholders, both in terms of number and type of organization. The local capacity of Tolikara Regency, one of the regencies in the Central Highlands region of Papua, is at a low level and needs to increase the capacity index with the initial step of increasing the capacity of local governments. The preparation of a disaster risk assessment document and outreach activities are an effort to increase the capacity of the area. The results of this document review serve as input for the local government to determine further policies. The FTSP-USTJ Study Center Team from Jayapura City was involved in this activity because there was no higher education institution in Tolikara Regency that could play a role as a stakeholder in disaster mitigation there.